2018
DOI: 10.1002/stem.2786
|View full text |Cite
|
Sign up to set email alerts
|

Store-Operated Calcium Entries Control Neural Stem Cell Self-Renewal in the Adult Brain Subventricular Zone

Abstract: The subventricular zone (SVZ) is the major stem cell niche in the brain of adult mammals. Within this region, neural stem cells (NSC) proliferate, self-renew and give birth to neurons and glial cells. Previous studies underlined enrichment in calcium signaling-related transcripts in adult NSC. Because of their ability to mobilize sustained calcium influxes in response to a wide range of extracellular factors, store-operated channels (SOC) appear to be, among calcium channels, relevant candidates to induce calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 76 publications
2
35
0
Order By: Relevance
“…Furthermore, morphological and immunohistochemical analyses identified a fate change in STIM1 knockdown NPCs where the balance between self-renewal and differentiation was altered significantly toward the latter. Mouse neural precursors with loss of function of the SOCE channel Orai exhibit very similar fate changes ( Prakriya et al, 2006 ; Lewis, 2007 ; Domenichini et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, morphological and immunohistochemical analyses identified a fate change in STIM1 knockdown NPCs where the balance between self-renewal and differentiation was altered significantly toward the latter. Mouse neural precursors with loss of function of the SOCE channel Orai exhibit very similar fate changes ( Prakriya et al, 2006 ; Lewis, 2007 ; Domenichini et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the attenuation of SOCE in mouse NPCs reduced their proliferation in vitro , as well as in the sub-ventricular zone (SVZ) of adult mouse brains in vivo ( Somasundaram et al, 2014 ). Moreover, a recent study demonstrated that pharmacological blockade of SOCE in mouse SVZ neural stem cells decreased proliferation and impaired self-renewal by shifting the type of SVZ stem cell division from symmetric proliferative to asymmetric ( Domenichini et al, 2018 ). Although mechanisms of neurogenesis are largely conserved among mammals, human neurogenesis shows some distinct attributes when compared to that of rodents, such as the presence of an astrocyte ribbon in the sub-ventricular zone (SVZ), higher turnover of hippocampal neurons and a rapid decline in the rate of neurogenesis with age ( Sanai et al, 2004 ; Knoth et al, 2010 ; Wang et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, Ca 2+ imaging experiments unveiled the existence in NSCs, of intercellular Ca 2+ waves that are propagated through gap junctions and that are used by NSCs to communicate with each other and with neighboring niche astrocytes both under physiological conditions (Lacar et al, 2011) and pathological conditions (Kraft et al, 2017). Live cell Ca 2+ imaging has also allowed to observe spontaneous Ca 2+ oscillations in NSC/progenitors from the V-SVZ (Domenichini et al, 2018) as well as spontaneous high-frequency transients in migrating neuroblasts (Maslyukov et al, 2018). Along with the prominence of transcripts related to the Ca 2+ pathway in NSCs, these data lend support to the essential role of Ca 2+ in NSCs and their progeny.…”
Section: Physiological Roles Of Ca 2+ In Nscs and Their Progeniesmentioning
confidence: 98%
“…In the V-SVZ, both Orai1 and TRPC1 have been detected along with STIM1 in NSCs and also in some neuroblasts (Skibinska-Kijek et al, 2009;Somasundaram et al, 2014;Domenichini et al, 2018). In these cells, SOCE could be triggered by various extracellular signals such as EGF that are used for cultures of NSCs (Reynolds et al, 1992;Somasundaram et al, 2014) or SDF1 that controls the tumor tropism of NSCs to glioblastoma (Zhao et al, 2008;Somasundaram et al, 2014).…”
Section: Store-operated Channels (Socs)mentioning
confidence: 99%
See 1 more Smart Citation